Subcutaneous and orally self-administered high-dose carprofen shows favorable pharmacokinetic and tolerability profiles in male and female C57BL/6J mice - Glasenapp, Aylina; Bankstahl, Jens P.; Bähre, Heike; Glage, Silke; Bankstahl, Marion (Frontiers in Veterinary Science, 2024)
IntroductionSurgical interventions in mice require appropriate pain relief to ensure animal welfare and to avoid influence of pain on research findings. Carprofen is a non-steroidal anti-inflammatory drug commonly used as an analgesic for interventions inducing mild to moderate pain in laboratory rodents. Despite its frequent use, species-specific data on pharmacokinetics (PK), side effects, and potential impact on behavioral pain indicators are limited.MethodsWe determined PK and tolerability profiles of carprofen in healthy male and female C57BL/6J mice (n = 42), administered at highest recommended doses via single subcutaneous (s.c.) injection (20 mg/kg) and oral self-administration (25 mg/kg/24 h) per drinking water (d.w.) for 5 days. Plasma concentrations were measured at various time points after the start of the treatment (n = 6 per time point), and side effects were evaluated using a modified Irwin test battery, hematology, and histopathology. Additionally, potential interference with cage-side behaviors commonly used for pain assessment, such as the mouse grimace scale, wheel running, burrowing, nesting, and grooming activity, was investigated.ResultsMaximum plasma concentrations of 133.4 ± 11.3 μg/ml were reached 1 h after single s.c. injection with an elimination half-life of 8.52 h. Intake from d.w. resulted in a steady state within 24 h after the start of the treatment with plasma levels of around 60 μg/ml over 5 days in both sexes. The medicated water was well-accepted, and increased d.w. intake was observed in the first 24 h after exposure (p < 0.0001). The Irwin test revealed only minor influence on tested behavior and physiological functions. However, during treatment via d.w., an increase in body temperature (p < 0.0001) was observed, as well as a reduction in voluntary wheel running activity by 49–70% in male mice. Moreover, grooming behavior was slightly affected. Hematology and histopathology were without pathological findings that could be attributed to carprofen treatment. High-dose carprofen can be considered safe and of favorable PK for both administration routes assessed in healthy C57BL/6J mice of both sexes. Further efficacy evaluation of carprofen as monoanalgesic or component of multimodal post-surgical regimens is clearly encouraged; however, the impact on behavioral markers used for pain assessment should be considered in this context.